CO oxidation over copper-chromium catalyst supported by indonesian zeolite - Suryo Purwono (Jurnal Rekayasa Proses, 2007)
The objectives of this paper are to oxidize CO on metal catalyst supported by natural zeolite and to find model for kinetic of CO oxidation that will accurately predict oxidation raJe under different temperatures and feed concentrations. The results shows that using Impregnation method, copper and chromium metals active components of the catalyst can be dispersed on the natural zeolite as catalyst support. The reaction rate measurements of catalytic oxidation of CO were done in the temperature range between 300 and 520oC using a differential micro-reactor. 'J1!e results show that the reaction rate depends strongly on the bed temperature and feed concentration and is not controlled by bulk phase mass transfer and pore diffusion.